High-Purity Copper Recovery from Fine Enameled Wires by Controlled Pyrolysis and Property Evaluation - Ez-zine, M.; Touaiher, I.; Choukri, O.; Saoudi, T. (Archives of Foundry Engineering, 2026)
*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-6a4b9991-224c-83eb-8190-d0e833776905-13" data-turn-id-container="request-6a4b9991-224c-83eb-8190-d0e833776905-13" data-testid="conversation-turn-256" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" data-conversation-screenshot-content=""> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="6e9a162b-ad6e-4978-8203-608bbf2dafd8" data-turn-start-message="true" data-message-model-slug="gpt-5-5-thinking"> The recovery of high-purity copper from used fine enameled wires without loss of mass is a valuable solution for foundries. Although this waste is widely available on the market, it remains undervalued due to significant losses during processing. This study presents an effective thermal recycling method for fine enameled copper wires, designed to remove insulation while preserving the metal's metallurgical properties. Pyrolysis was performed between 450°C and 900°C with constant holding phases, followed by remelting in an induction furnace. Chemical, microstructural (SEM and optical), and electrical analyses identified an optimal temperature of 550°C with a holding time of 82 minutes, based on a well-defined thermal sequence. At this temperature, the enamel is completely decomposed, resulting in copper with 99.5% purity before melting and a recovery rate exceeding 99%. After melting, the 8 mm wire produced had a uniform microstructure and an average conductivity of 97.2% IACS, aligning with industrial standards for wire drawing (electrical applications). In contrast, direct melting of untreated wires caused inclusions, metal losses, and reduced conductivity. The proposed process, which is simple and cost-effective, offers an efficient way to recycle this type of waste and supports the circular economy.